Auto-tuning of PV controllers to improve the speed response and stability of the P&O algorithm - Ortiz Valencia, Paula Andrea; Carlos Andrés Ramos Paja (Ingeniería e investigación, 2015)
This paper proposes an auto-tuning control system to ensure a fast response of the photovoltaic (PV) voltage by reducing the perturbation time of a P&O algorithm. This solution accelerates the tracking of the maximum power point and, at the same time, guarantees the system stability, which increases the amount of energy produced by the PV system. The control system consists of three cascaded controllers: a P&O algorithm dynamically parameterized by the adaptive law in order to guarantee stability; an adaptive PI controller whose parameters are modified by the adaptive law, depending on the operating conditions, to reduce the settling time of the system as much as possible; and a sliding mode current controller to mitigate environmental and load perturbations and ensure global stability. The design of the new control structure is supported by mathematical analyses and validated with simulations performed in PSIM in order to demonstrate the robustness of the proposed solution.